SANKSI PIDANA TERHADAP KORPORASI SEBAGAI PRODUSEN NARKOTIKA - Hamja, Hamja (Universitas Wiralodra, 2013)
Law No. 35 of 2009 on Narcotics is not effective in the application of criminal sanctions for corporations that produce narcotics, for corporations that commit these crimes, in addition to the main criminal is a criminal fine of two times the criminal penalties under Article 113, Article 115, Article 120, and Article 135. Implementation of Act No. 35 of 2009 on Narcotics yet fully implemented. In the case of a drug crime prosecution proved occur compromises containing kickbacks. Since the process of catching up in the police investigation is common bargaining in the application section. While negotiations punishment was too often happens under the table between defendant, prosecutor and judge.